1972
DOI: 10.1073/pnas.69.10.2914
|View full text |Cite
|
Sign up to set email alerts
|

Dog Homologue of Human β 2 -Microglobulin

Abstract: The amino-acid sequence of human ,3g-microglobulin, a protein of 100 residues, is related to parts of the constant region of IgG heavy chain. The dog homologue of human ,B2-microglobulin has now been isolated and its amino-acid sequence has been partially determined. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

1977
1977
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 8 publications
1
18
0
Order By: Relevance
“…The only previous report of isolation of dog β2-m was that of Smithies and Poulik [23]. Their report described using anion exchange to purify dog β2-m after its separation from other urinary proteins by gel filtration chromatography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only previous report of isolation of dog β2-m was that of Smithies and Poulik [23]. Their report described using anion exchange to purify dog β2-m after its separation from other urinary proteins by gel filtration chromatography.…”
Section: Discussionmentioning
confidence: 99%
“…However, their report did not discuss catabolism of dog β2-m in the dog kidney. To facilitate further studies, an efficient method of isolating large quantities of β2-m is being sought, of Smithies and Poulik [23] was the first to isolate dog β2-m. However, the amino acid sequence of dog β2-m elucidated contained only 42 N-terminus residues and a number of obscure residues [23].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since its discovery in human urine in 1968, the overall properties, synthesis, and amino acid sequence of this protein have been characterized (2,(8)(9)(10)(11). Similar proteins have been detected in a variety of species, and all appear as a single polypeptide [molecular weight (Mr) = 11,600], with few differences in amino acid sequence among the proteins from different species (2,3,(12)(13)(14).…”
mentioning
confidence: 99%
“…Since its discovery in human urine in 1968, the overall properties, synthesis, and amino acid sequence of this protein have been characterized (2,(8)(9)(10)(11). Similar proteins have been detected in a variety of species, and all appear as a single polypeptide [molecular weight (Mr) = 11,600], with few differences in amino acid sequence among the proteins from different species (2,3,(12)(13)(14).Comparison of the amino acid sequence and other features of human #32-microglobulin with immunoglobulins (1, 15) has indicated that it closely resembles the constant homology regions (16) of immunoglobulins G, M, and E. In intact immunoglobulin molecules, each homology region is closely associated with the corresponding homology region of another immunoglobulin chain in pairs of domains (16, 17), whereas ,62-microglobulin is found associated with the heavy chain of HLA or H-2 antigens or the closely related thymus leukemia antigen (4-7, 18, 19), suggesting that such paired domains may be structural features of these cell surface molecules. In solution,…”
mentioning
confidence: 99%